Bio-Oil Production Using Waste Biomass via Pyrolysis Process: Mini Review (Jurnal Bahan Alam Terbarukan, 2022)
Pyrolysis process using abundantly available biomass waste fabric is a promising, renewable, and sustainable energy supply for bio-oil production. In this study, the pyrolysis of waste biomass determines the highest yield of diverse parameters of material type, temperature, reactor, method, and analysis used. From the differences in the parameters stated above, there is  an opportunity to select the proper parameters to get the desired nice and quantity of bio-oil and the very best bio-oil yield. The maximum yield of each bio-oil product for pyrolysis primarily based on the above parameters was 68.9%; 56.9%; 44.4%; 44.16%; 41.05%; 39.99%. The bio-oil made out of pyrolysis was changed into analyzed using GC-MS, ft-IR, NMR, TGA, SEM, Thermogravimetric analysis, HHV, FESEM evaluation methods and the substances used had been plastic, seaweeds, oat straw, rice straw , water hyacinth, timber sawdust, sawdust, microalgae.